Implementasi Proses Bisnis Dalam Upaya Penerapan Green Hospital - S Sofiyanurriyanti (Jurnal Teknik Industri, 2017)
The hospital is a public health service institution. The hospital environment is an aspect that also needs to be considered and managed well. One effort to support the management of a healthy, clean and friendly environment is a green hospital. The application of green hospital covers environment with the green environment, water usage efficiency, electric energy, material use and waste reduction. Evaluation of environmental impact assessment There are several steps including characterization, damage assessment, normalization, weighting and the single score. The methods used under Eco Indicator 99 of some environmental impacts include carcinogens, respiratory organics, climate change, radiation, the ozone layer, ecotoxicity, acidification/eutrophication, land use, minerals, and fossil fuel. While to assess the environmental impact of waste can be seen from the results of life cycle assessment based on characterization, normalization weighting, and the single score. The environmental impacts generated in hospitals affecting human health is 0.153209 Pt, eco system quality of 0.178514 Pt, and resources 0.359308 Pt.